Anti Xa activity after high dose LMWH thrombosis prophylaxis in covid 19 patients at the intensive care unit. Issue 196 (December 2020) - Vlot, E.A.; Van den Dool, E.J.; Hackeng, C.M.; Sohne, M.; Noordzij, P.G.; Van Dongen, E.P.A.
Abstract: Introduction: Coagulopathy in Coronavirus disease 2019 (covid-19) has been demonstrated by an increase in D-dimer, prothrombin time (PT), fibrinogen and factor VIII. Venous thromboembolic events are a common abnormality in patients with covid-19. We evaluate the results of intensive care unit (ICU) thrombosis prophylaxis of 5700 international unit (IU) nadroparin low molecular weight heparin (LMWH) twice daily. Methods: After introduction of this high-dose pharmacological thrombosis prophylaxis twice weekly anti-factor Xa (anti Xa) concentrations and results from routine laboratory and viscoelastic hemostatic tests in 16 ICU covid-19 patients were evaluated. Results: During one week, median peak anti Xa activities were 0.38 [0.16–0.45] and 0.38 [0.20–0.58] at time point 1 and 2 respectively. Laboratory coagulation tests showed PT, AT and platelet count (PltC) values within normal range and markedly increased D-dimer and fibrinogen levels. Viscoelastic tests showed a maximum clot strength just above normal reference value, while fibrin clot strength was strongly increased. The overall contribution of fibrin to clot strength was high with 71 [56–85]%. Conclusion: Anti Xa activity was within the target range of pharmacodynamic endpoint for covid-19 patients but viscoelastic tests still demonstrated a procoagulant pattern.